2016
DOI: 10.1186/s13098-016-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

Early diabetes screening in women with previous gestational diabetes: a new insight

Abstract: BackgroundGestational diabetes mellitus (GDM) is a risk factor for the development of diabetes mellitus (DM). However, there is a low return rate for this screening, so it is important to search for earlier methods for evaluation after delivery, to increase the number of pregnant women screened, so you can start the treatment or prevention of these early comorbidities. To determine the accuracy of the 75 g 2-h oral glucose tolerance test (OGTT) performed between 48–72 h after delivery for the diagnosis of DM u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…The results of this study showed a significant, temporary improvement in maternal fasting glucose in all subcategories of glycaemia 24–72 hours following delivery. In contrast to similar published work, early post-delivery glucose testing was not found to be a feasible alternative to the standard of care 4-12-week postpartum visit in women with HFDP within our population group [ 14 , 17 – 21 ]. The study failed to identify high risk individuals and did not demonstrate that in-hospital fasting glucose could help to direct resources to those most in need of surveillance.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The results of this study showed a significant, temporary improvement in maternal fasting glucose in all subcategories of glycaemia 24–72 hours following delivery. In contrast to similar published work, early post-delivery glucose testing was not found to be a feasible alternative to the standard of care 4-12-week postpartum visit in women with HFDP within our population group [ 14 , 17 – 21 ]. The study failed to identify high risk individuals and did not demonstrate that in-hospital fasting glucose could help to direct resources to those most in need of surveillance.…”
Section: Discussioncontrasting
confidence: 93%
“…Nabuco and colleagues (2016) compared the outcome of an early postpartum (48-72 hours after delivery) OGTT with the standard assessment at 6 weeks. They aimed to determine cut-off glucose values at this time point in order to identify the presence of pre-diabetes and T2DM at 6 weeks [17] . The prevalence of diabetes and pre-diabetes in their cohort of 82 women with GDM based on an OGTT performed at 48-72 hours after birth was 3.7% and 32.9%, respectively, whereas the prevalence based on the 6 week OGTT was 8.5% and 20.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, our sample size could be a limitation to the investigation of these factors. A study conducted also in Rio de Janeiro found that only a previous history of GDM was significantly higher in mothers who returned 6 weeks later for performing the OGTT [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an important risk factor for permanent or future development of glucose intolerance or T2DM in the postpartum period. About 3–65% of women with previous GDM present T2DM within 5–16 years after pregnancy, depending on the methods used for screening and the studied population [ 2 , 3 ]. Postpartum glucose tolerance status after GDM varies from 1.1 to 25.3% for T2DM, and from 2.2 to 42.3% for both impaired glucose tolerance and impaired fasting glycemia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Earlier studies have addressed ~3-65% of GDM women developed type 2 diabetes mellitus (T2DM) during 5-16 years after the index pregnancy. 2 Human and Animal studies research revealed GDM and T2DM have characterized β-cell dysfunction, insulin resistance and defects in insulin action. 3 T2DM and GDM share the common pathophysiology and predisposing factors.…”
Section: Introductionmentioning
confidence: 99%